Impact of virtual reality on pain management in transrectal MRI-guided prostate biopsy - Perenic, Emma; Grember, Emilie; Bassard, Sébastien; Koutlidis, Nicolas (Frontiers in Pain Research, 2023)
Background The beneficial effect of virtual reality (VR) on pain management in the context of transrectal MRI-guided prostate biopsy is not well established. However, it remains unclear whether an adjunctive of VR also improves pain management. This study aimed to evaluate the impact of VR as adjunctive in pain management in transrectal MRI-guided prostate biopsy (PB). Methods We retrospectively evaluated the pain intensity incidence in the 153 patients with PB indication (of which 102 were naïve of PB) who were admitted to our hospital since the acquisition of the Healthy Mind virtual reality headset on 19 January 2021. Results Baseline characteristics of patients who received local anesthesia with 1% lidocaine periprostatic nerve block (PPNB) (Group SOC, N = 78) and patients who received VR associated with PPNB (Group VR, N = 75) were largely similar. One PB with general anesthesia was excluded. The mean pain score at day zero was respectively 3.4 (±2.5) and 2.9 (±2.3) for SOC and VR (p = 0.203). However, the mean pain score at day zero was significantly lower in naïve PB patients with VR [2.7 (±2.0)] than in naïve PB patients with SOC [3.8 (±2.5), p = 0.012] when patients were stratified in PB status. Similar results were found on day 3 for the analysis including naïve-PB patients with SOC vs. with VR [0.4 (±2.5) vs. 0.2 (±2.0); p = 0.023)]. Conclusions The pain intensity was significantly lower in naïve PB patients with VR than in naïve PB patients with SOC. There were no side effects from VR and tolerability was excellent.